Research on Feedforward Compensation Control Strategy of Electro-hydraulic Servo System for Underwater Manipulator - WANG Hongfei; YAN Yun; LUO Lingbo; YAN Hongwen (Kongzhi Yu Xinxi Jishu)
It analyzed an electro-hydraulic servo system of typical high-performance underwater manipulator and established mathematical models of the electro-hydraulic servo system when taking Titan-4 7-function manipulator of Schilling company as an example. According to the working characteristics of the underwater manipulator, by using the three-state control technology widely used in seismic simulation shaking table for reference, a servo control strategy was designed which adopts the method of PID and feed-forward compensation control to achieve fast response and high precision control effect. Matlab/Simulink simulation results show that the feed forward compensation control algorithm based on the three-state control technology can effectively improve response speed of the system and expand operation ability of the manipulator in complex underwater environment.